A Survey of Studies on Discourse Structure and Relation - Huang, Nianyi (Transactions on Computer Science and Intelligent Systems Research, 2024)
Discourse Analysis aims at high-level semantic and structural analysis. Discourse structure analysis and relation recognition are two key tasks in discourse analysis research, while discourse analysis plays an important role in studying the structure and semantic content of texts. This paper firstly introduces the Rhetorical Structure Theory (RST) and the Penn Discourse TreeBank (PDTB) annotation standards and its corresponding resources establishment of each corpus. Then the mainstream models of discourse structure and relation are expounded. In the last part, the opportunities and challenges of discourse analysis are discussed by combining with the mainstream large language model ChatGPT. In addition, the development prospect of discourse analysis is explored by summarizing the related studies.